2002
DOI: 10.1007/s001980200071
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fracture Risk and Proximal Femur Geometry from DXA Scans

Abstract: In this retrospective study of hip fracture risk evaluation from hip dual-energy X-ray absorptiometry (DXA) scans, our objectives were to determine which part of the femoral neck length contributes most to the fracture risk and to define a geometric parameter better than hip axis length (HAL) for discriminating hip fracture patients. Forty-nine Caucasian women with a nontraumatic femoral neck fracture were matched on age to 49 normal women and on both age and femoral neck bone mineral density (BMD) to 49 unfra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 42 publications
7
80
1
4
Order By: Relevance
“…Nevertheless, it should be pointed out that in males, a statistically significant inverse relationship between the NSA and FN-BMD was found, as already reported by others, 14,18 which was not observed in females. 26,29 The latter finding was also reported by other authors, 9,30 who found NSA to be an independent predictor of hip fracture in females. Therefore, it may be that the negative correlation of FN-BMD with NSA leads BMD to capture some of the effects of NSA on hip fracture; thus explaining, at least partially, the disagreement between males and females regarding the independence of the ability of NSA to predict hip fracture.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, it should be pointed out that in males, a statistically significant inverse relationship between the NSA and FN-BMD was found, as already reported by others, 14,18 which was not observed in females. 26,29 The latter finding was also reported by other authors, 9,30 who found NSA to be an independent predictor of hip fracture in females. Therefore, it may be that the negative correlation of FN-BMD with NSA leads BMD to capture some of the effects of NSA on hip fracture; thus explaining, at least partially, the disagreement between males and females regarding the independence of the ability of NSA to predict hip fracture.…”
Section: Discussionsupporting
confidence: 78%
“…It was automated in DXA instruments in 1994 [37]. Many subsequent studies have confirmed these original findings [23,[38][39][40][41][42]. Gnudi et al reported that women with femoral fractures had longer HAL, wider FND and larger NA than controls [40].…”
Section: Discussionmentioning
confidence: 91%
“…A recent innovation in non-invasive bone mass measurement is DXA which offers a lower absorbed radiation dose, higher spatial resolution and greater scan speed [11]. There is also incontrovertible evidence that BMD as measured by DXA, particularly at the proximal femur, is the main determinant of hip fracture risk [12].…”
Section: Methodsmentioning
confidence: 99%